THE EFFECT OF CHITOSAN WITH AVERAGE MOLECULAR WEIGHT ON THE QUALITY OF PAPER - Iskandarov, Adham Isroil o‘g‘li; Sattarkulov , Lazizbek Abror o‘g‘li; Zokirova, Zilola Qaxramon qizi (Educational Research in Universal Sciences, 2023)
The study examined the use of low and medium molecular weight chitosan to reduce the water-absorbing properties of paper and increase its strength and smoothness.